The incidence of intestinal obstructive diseases in selected veterinary clinics and hospitals in South Western Nigeria (2011)
Intestinal obstructive diseases are medical and surgical emergencies which require precise diagnosis and rapid surgical intervention. They are characterized by severe hypovolemia and septic shock secondary to devitalization of the intestinal wall. The consequent surgical complications such as ileus, adhesions and short bowel syndrome with resultant death of the patients also pose management challenges to the clinician. This study investigated the incidence of intestinal obstructive diseases in some animals presented at selected Veterinary Hospitals and Clinics in southwestern Nigeria between 1998 and 2008. Records of surgical cases were grouped into 11 categories and further grouping of intestinal obstructive conditions in small and large animals were presented using descriptive statistics. Intestinal obstructive conditions ranked 8th among the 11 categorized surgical conditions, and 7.0 % of the surgical cases which were presented between 1998 and 2008. Most of the intestinal conditions such as intussusception, volvulus and torsion were strangulating obstructive conditions and occurred more in small than large animals. Hernia ranked highest among the surgical conditions, followed by intussusception, volvulus and rectal prolapse in that order. The intestinal conditions were more prevalent in post mortem records and in small animals than in large animals. The findings in this study showed that intestinal surgical conditions are not uncommon in Veterinary hospital and clinics in the study area. It further showed that the management of intestinal surgical conditions is still a major challenge in some Veterinary hospital and clinics in Nigeria